PEMBENTUKAN RUANG BERSAMA DAN RUANG TERBUKA HIJAU DI LINGKUNGAN BABATAN PILANG RT. 003 RW. 005 - Heristama Anugerah Putra; Josephine Roosandriantini (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2021)
The area of open land in the City of Surabaya is decreasing from year to year. This is influenced by the number of settlements and housing that have begun to emerge and develop, thus increasing the population level in an area. Humans are by nature social creatures. Can not be separated from other individuals and need each other. Individual someone indirectly lives together with the surrounding environment. This is what triggers that each individual must be social to one another. However, along with the times and technological advances today, many individuals often forget this and think more about their respective interests. Time to gather and meet face to face with neighbors, chat with each other directly or with the surrounding environment is also very minimal. Broadly speaking, the Babatan Pilang community is individual. The background to the problems that have been previously described is the basis for this community service to be able to provide input to the community of Babatan Pilang RT. 003 RW 005. The purpose of this community service is to help the community or housing residents to restore and create a social society. This community service program is carried out by creating and arranging common spaces for socializing.